Selected aspects of the design of special monolithic carbide milling cutters for austenitic steels - Małek Marcin; Grabowski Marcin; Skoczypiec Sebastian (Technical Transactions, 2023)
In many machining applications, the appropriate selection of cutting tools in relation to the type of material being machined, the machining parameters and the required shape and dimensional accuracy is of particular importance. This especially applies to operations requiring the use of specific tools, i.e. tools that are not included in the standard offer but are tailor-made according to the individual needs of the customer. The article focuses on the machining problems of selected austenitic grades of stainless steel and the selection of technologies (i.e. machining parameters and strategies and tool geometry) concerning the design and use of special monolithic carbide milling cutters. The possibilities of manufacturing elements from austenitic steels with high shape and dimensional accuracy and high surface layer quality are limited. Due to their high ductility, the tendency to create growths on the cutting edge and the high compression strength coefficient, these materials pose a serious technological challenge. The analysis of phenomena presented in the article forms the basis for developing guidelines for designing the machining process using special monolithic carbide cutters dedicated for specific applications.